Thrombospondin-1 mitigates osteoarthritis progression by inhibiting mechanical stress-induced chondrocyte ferroptosis via the integrin/YAP pathway - Shaoyi Wang; Shaoyi Wang; Xiaocong Zhou; Fujian Zhang; Haoxin Zhai; Yuanqiang Zhang; Yuanqiang Zhang; Yongyuan Guo (Frontiers in Immunology)
IntroductionOsteoarthritis in weight-bearing joints significantly impacts the quality of life in middle-aged and elderly individuals. Abnormal mechanical stress can induce chondrocytes ferroptosis, thereby accelerating the progression of osteoarthritis. In this study, we investigated the therapeutic effects of targeting chondrocyte ferroptosis to delay the progression of osteoarthritis and identified a potential therapeutic target.MethodsThrough transcriptomic sequencing analysis, we identified a potential association between thrombospondin-1 (THBS1) and mechanical stress-induced chondrocyte ferroptosis. In this study we used via adeno-associated virus-mediated THBS1 overexpression, cell pressurization model and GPX4-conditional knockout (Col2a1-CreERT: GPX4flox/flox) mice to verify the regulatory effect of THBS1 on chondrocytes ferroptosis. Additionally, protein interaction network analysis, immunofluorescence co-localization, and co-immunoprecipitation were conducted to investigate the mechanism by which THBS1 modulates chondrocytes ferroptosis.ResultsThe expression of THBS1 protein was reduced in load-bearing cartilage tissue in humans. THBS1 suppressed chondrocytes ferroptosis induced by excessive mechanical stress. Immunofluorescence co-localization and CO-IP experiments indicated that integrin αV/β1 serves as the membrane receptor through which THBS1 regulates chondrocyte ferroptosis under mechanical stress. Upon activation, integrin αV/β1 modulated YAP1 nuclear translocation, thereby affecting GPX4 activity. Intra-articular injection of THBS1 synthetic peptides effectively reduced cartilage damage in mouse OA models, protecting articular cartilage and slowing the progression of osteoarthritis.DiscussionOur results indicate THBS1 regulates mechanical stress-induced chondrocyte ferroptosis through the Integrin/YAP pathway. Furthermore, THBS1 effectively slows the progression of osteoarthritis and protects articular cartilage.